Birth control, pregnancy and abortion among adolescents in Chiang Mai, Thailand - Arunrat Tangmunkongvorakul (2018)
The authors studied more than 1750 young urban Chiang Mai residents regarding pre-marital sex, contraception and reproductive health outcomes. Almost two-thirds of the males had had sexual intercourse, compared to one-third of the females. Withdrawal was the most popular method of birth control followed by condom use. There were more females (30.5 per cent) reporting that they had been pregnant than males (17.5 per cent) reporting that they had caused pregnancies. Twothirds of the respondents who had experienced or caused pregnancy reported that it ended in abortion. Almost half of those who had experienced abortion had induced it themselves, usually using illegal abortifacients. One-third went to a private clinic or hospital illegally. Self-induced abortions were sometimes associated with complications that were treated with pharmacy medications or severe complications requiring hospital treatment. Adolescents in northern Thailand need improved sexual health services and programmes. To be effective though, attention should also be given to underlying cultural attitudes toward sexuality and young people, especially women. © 2011 Taylor & Francis.